Sleeping beauty transgenesis in cattle - Garrels, Wiebke (2014)
Transposon-mediated transgenesis is a well-established tool for genome modification in small animal models. However, translation of this active transgenic method to large animals warrants further investigations. Here, the Sleeping Beauty (SB) transposon system was assessed for stable gene transfer into the cattle genome. The transposon plasmids encoded a ubiquitously active CAGGS promoter-driven Venus reporter and a lens-specific α A-crystallin promoter driven tdTomato fluorophore, respectively. The helper plasmid carried the hyperactive SB100x transposase variant. In total, 50 in vitro-derived zygotes were co-injected (Garrels et al. 2011 PLoS ONE 6; Ivics et al. 2014 Nat. Protoc. 9) and cultured up to blastocyst stage (Day 8). Two blastocysts were Venus-positive and were transferred to synchronized heifers, resulting in one pregnancy. The resulting calf was normally developed and vital; however, it died shortly after cesarean section due to spontaneous bleeding from an undetected aneurism. Phenotypic analysis suggested that the calf was indeed double-transgenic, showing widespread expression of Venus and lens-specific expression of tdTomato. Genotyping and molecular analyses confirmed the integration of both reporter transposons and the faithful promoter-dependent expression patterns. Subdermal tissue of an ear biopsy was used to culture fibroblasts, which were employed in somatic cell nuclear transfer experiments. In total, 39 embryos were reconstructed, of which 34 underwent cleavage, and at the end of culture 12 morulas and 12 blastocysts were obtained. Ten of the blastocysts were Venus positive, and embryo transfer of Venus-positive blastocysts is planned. In summary, we showed that the cytoplasmic injection of SB components is a highly efficient method for transgenesis in cattle. Due to the modular composition of SB plasmids, even double transgenic cattle can be generated in a one-step procedure. Importantly, the SB-catalyzed integration seems to favour transcriptionally permissive loci in the genome, resulting in faithful and robust promoter-dependent expression of the transgenes. The transposon constructs carry heterospecific loxP sites, which will be instrumental for targeted insertion of functional transgenes by Cre recombinase-mediated cassette exchange.